Incidence and Risk Factors of Dry Eye in Children and Adolescents With Diabetes Mellitus: A 3-Year Follow-Up Study - Chen, Zhangling; Xiao, Ying; Qian, Yu; Lin, Qiurong; Xiang, Zhaoyu; Cui, Lipu; Sun, Jiaqi; Li, Sicong; Qin, Xinran; Yang, Chenhao; Zou, Haidong (Frontiers in Medicine, 2021)
Purpose: To investigate the incidence and risk factors of dry eye in diabetic children over a period of 3 years. Methods: Diabetic children and adolescents (age: 3–14 years) from the Shanghai Children and Adolescent Diabetes Eye (SCADE) study cohort who did not have dry eyes in January 2018 were followed-up for 3 years and re-examined in January 2021, and the incidence rate and risk factors for dry eye were calculated. Results: Nine of 40 diabetic children and adolescents followed-up for 3 years were diagnosed with dry eye, resulting in a 3-year incidence rate of 22.5% and an annual mean incidence rate of 7.5% for dry eye. Univariate regression analysis confirmed that long duration of diabetes mellitus (odds ratio [OR] = 1.80), decreased corneal sensation (OR = 25.60), eye pain (OR = 12.27), and parental dry eye (OR = 15.99) were the risk factors for dry eye in diabetic children and adolescents. Conclusions: The incidence of dry eye in diabetic children and adolescents is high, and corresponding measures should be taken to reduce the incidence of dry eye in the susceptible population.